2017
DOI: 10.1083/jcb.201701034
|View full text |Cite
|
Sign up to set email alerts
|

PICK1 regulates AMPA receptor endocytosis via direct interactions with AP2 α-appendage and dynamin

Abstract: Fiuza et al. report that PICK1 localizes to clathrin-coated pits and makes direct, functional interactions with the endocytic adapter complex AP2 and dynamin. The PICK1–AP2 interaction is required for clustering AMPA receptors at endocytic sites and for consequent AMPA receptor endocytosis, defining PICK1 as a cargo-specific endocytic accessory protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 62 publications
3
67
0
Order By: Relevance
“…Recently, PICK1 was also shown to interact with a central player in clathrin-mediated endocytosis, the adaptor protein AP2, which bridges cargo proteins and clathrin. This interaction is required for AMPAR clustering and internalization upon NDMAR stimulation [ 133 ].…”
Section: Pdz Domain-containing Interactantsmentioning
confidence: 99%
“…Recently, PICK1 was also shown to interact with a central player in clathrin-mediated endocytosis, the adaptor protein AP2, which bridges cargo proteins and clathrin. This interaction is required for AMPAR clustering and internalization upon NDMAR stimulation [ 133 ].…”
Section: Pdz Domain-containing Interactantsmentioning
confidence: 99%
“…In addition, PICK1 was also able to promote dynamin polymerization by interacting with its GTPase domain. This work interestingly suggests that PICK1 not only links AMPA-Rs to the endocytic machinery to enhance its internalization but that it is directly able to promote the activity of two crucial players in endocytosis events, AP-2 and dynamin (Fiuza et al, 2017 ).…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…Recently, Fiuza et al ( 2017 ) further elucidated the mechanism through which PICK1 mediates GluA2 removal from the surface membrane. The authors showed that PICK1 is recruited to clathrin-coated pits by interacting with the adaptor protein complex AP-2, an association enhanced by LTD-like NMDA-R activation.…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…(Praefcke et al, 2004 ; Daumke et al, 2014 ; Suetsugu et al, 2014 ). A recent addition to the BAR domain proteins identified as an α-appendage interactor is protein interacting with C-Kinase 1 (PICK1; Figure 1B ; Fiuza et al, 2017 ), which has a well-established role in decreasing the surface and synaptic levels of GluA2-containing AMPARs (Terashima et al, 2004 ). The PICK1 PDZ domain binds the C-terminal tail of AMPAR subunit GluA2, and disrupting this interaction with competing peptides or by mutagenesis inhibits both constitutive and NMDAR-stimulated AMPAR internalization and LTD in hippocampal neurons (Daw et al, 2000 ; Osten et al, 2000 ; Iwakura et al, 2001 ), as well as cerebellar LTD.…”
Section: Early Stages Of Clathrin-coated Pit Formationmentioning
confidence: 99%
“…PICK1 binds directly to AP2 with similar consensus motifs (FxDxF and DxF) to numerous other endocytic accessory proteins (Praefcke et al, 2004 ; Olesen et al, 2008 ; Fiuza et al, 2017 ). Mutating the critical aspartate residues to alanines in PICK1 disrupts AP2 binding and consequently inhibits both constitutive and NMDAR-dependent internalization of endogenous GluA2-containing AMPARs (Fiuza et al, 2017 ).…”
Section: Early Stages Of Clathrin-coated Pit Formationmentioning
confidence: 99%